Aspectos morfológicos e lesões em olhos de animais domésticos e selvagens - Teodoro, Tamires Goneli Wichert (2019)
The eyes are sensory organs responsible for capturing visual stimuli and the transmission to the encephalon where occurs the transduction of these signs. They have a spherical shape, with distinct layers of photosensitive tissues. The histopathologic examination of the eye is considered complex and specific, due to the various particularities of each tissue that compose it. The eyeball consists of three tunics arranged concentrically; the external layer is formed by sclera and cornea; medium layer, composed of iris, ciliary body and choroid; and inner layer, the retina. Comparative Ocular Pathology is a specialty that is still underestimated, compared with the study of other tissues and systems in animals. This reality shows the importance of establishing routine analysis, both macroscopic and histological, of the eyes. This study aims to contribute to the knowledge of the morphological characteristics of the eyes and the macroscopic and histopathological findings of the ocular lesions. The ocular bulbs of all animals received for necropsy at the veterinary pathology Department of Veterinary Medicine, at Universidade Federal de Lavras, in the period from September 2017 to February 2019 and the samples of bulbs and adnexa of the eye received at the SPV for histopathological exam, in the period of 2014 to 2019, were included in these study. In total, 574 pairs of eyeballs were collected for microscopic examination and histopathologic analysis. In the macroscopic examinated, measurements were made to obtain morphological ocular data for the evaluated species. Of the 574 pairs of eyeballs, 152 were measured. Ocular alterations were thoroughly described and related to other morphological findings in animals examined. Histopathologic examinations of the eyeball and adnexa of the eye from surgical exeresis totaled 89 cases. In cases of necropsy, inflammatory alterations predominated, especially in dogs, which were related to leishmaniasis, whereas in cases of surgically exeresis samples predominated neoplasms cases. Also, histological peculiarities observed in sheep and goat sclera were described.